2022
DOI: 10.1292/jvms.21-0562
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis of plasma and intramuscular adipose tissue between Wagyu and Holstein cattle

Abstract: In this experiment, we studied the effects of breed differences in intramuscular adipogenic capacity on the metabolomic profiles of plasma and intramuscular adipose tissue between Wagyu (high intramuscular adipogenic capacity) and Holstein (low intramuscular adipogenic capacity) using capillary electrophoresis time-of-flight mass spectrometry (CE-TOFMS). We showed that the intramuscular fat content, intramuscular adipocyte size and the expression of adipogenic transcription factor (C/EBPβ and C/EBPα) of Wagyu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…These results suggest that plasma metabolites detected by metabolome analysis reflect the breed differences of body fat contents between Wagyu and Holsteins. We also showed that the intramuscular adipose tissue metabolites detected at significantly different levels between Wagyu and Holsteins were associated with the hepatic steatosis and muscular dystrophies reported in humans (Yamada et al, 2022). Deposition of adipose tissue within skeletal muscle and liver are categorized as ectopic fat (Després et al, 2008;Després & Lemieux, 2006).…”
Section: Metabolome Analysismentioning
confidence: 67%
See 2 more Smart Citations
“…These results suggest that plasma metabolites detected by metabolome analysis reflect the breed differences of body fat contents between Wagyu and Holsteins. We also showed that the intramuscular adipose tissue metabolites detected at significantly different levels between Wagyu and Holsteins were associated with the hepatic steatosis and muscular dystrophies reported in humans (Yamada et al, 2022). Deposition of adipose tissue within skeletal muscle and liver are categorized as ectopic fat (Després et al, 2008;Després & Lemieux, 2006).…”
Section: Metabolome Analysismentioning
confidence: 67%
“…We hypothesized that the differences of intramuscular adipogenic capacity between Wagyu and Holstein would affect the metabolomic profiles of plasma and intramuscular adipose tissue. We showed that the plasma metabolites detected at significantly different levels between Wagyu and Holsteins were associated with the obesity and obesity‐associated phenotypes (tricarboxylic acid cycle, lipid synthesis, fatty acid metabolism, diabetes, and glucose homeostasis) reported in humans (Yamada et al, 2022). Body fat contents of Wagyu were higher than that of Holsteins (Matsuzaki et al, 1997; Yamada et al, 2009).…”
Section: Metabolome Analysismentioning
confidence: 91%
See 1 more Smart Citation
“…Certain metabolites in the TCA cycle increase the IMF content in Wagyu cattle. 35 The key metabolites enriched in these pathways revealed that 3-iodo-L-tyrosine is higher in the Wagyu cross F1 generation and Pingliang Red Cattle. It can stimulate the production of thyroid hormones, which stimulate the expression of fatty acid biosynthetic pathways such as acetyl coenzyme A carboxylase and fatty acid synthase in the liver, resulting in higher UFA in Wagyu cross F1 generation and Pingliang Red Cattle.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The KEGG analysis revealed that compared to the Simmental cattle, tyrosine metabolism, 2-oxocarboxylic acid metabolism, thyroid hormone synthesis, and citrate cycle (TCA cycle) were significantly enriched metabolic pathways in the Pingliang Red Cattle and Wagyu cross F1 generation. Certain metabolites in the TCA cycle increase the IMF content in Wagyu cattle . The key metabolites enriched in these pathways revealed that 3-iodo- l -tyrosine is higher in the Wagyu cross F1 generation and Pingliang Red Cattle.…”
Section: Discussionmentioning
confidence: 99%